Zinc priming promotes seed germination and seedling vigor of rice - Chanakan Prom-U-Thai (2018)
The present study evaluated effects of seed zinc (Zn) priming at concentrations from 0 to 25 mM ZnSO4 on seedling vigor and viability in rice (Oryza sativa L.). Zinc priming substantially increased Zn concentration in the husk, but not in brown rice. The movement of primed Zn from the husk into the inner layers of rice seed during germination was suggested by Zn concentration declining in the husk coinciding with the increase in brown rice over time (r = -0.62; p < 1%), which did not happen in unprimed seed. Zinc priming significantly enhanced seedling growth and development up to 5 mM. Germination rate, root number, and dry weight were much higher than in unprimed seed, but higher Zn concentrations (10 and 25 mM) depressed seedling vigor. Priming rice seed with 2.5 mM Zn also improved the germination rate of rice in a Zn-deficient soil, with or without soil Zn application. The results confirm that priming rice seed with Zn can improve germination and seedling vigor and for the first time show how Zn requirement of germinating rice seed and seedlings can be met by the prime Zn accumulated in the husk. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.